The Birth of the Meiji Empire (明治大帝の誕生): The State Shintoization of the Imperial Capital(帝都の国家神道化) - Sam-Hun Park (Journal of Dharma, 2025)
Understanding the meaning of State Shinto is the key to elucidating the modern Japanese history in religion and spirit. It makes clear how the self-identity of the Japanese people has transformed since the Meiji Restoration and to the present. In this sense, ‘State Shinto’ can be considered a core concept for describing the overall picture of the spiritual life of the Japanese, which so-called theories on Japanese people or Japanese culture have yet to fully explain. In this book, the author suggests the concept of ‘Divine Emperor’ as a new framework for understanding State Shinto and introduces ‘Emperor Meiji’ as its historical embodiment.